2020
DOI: 10.1371/journal.pone.0232634
|View full text |Cite
|
Sign up to set email alerts
|

Are serum levels of inhibin A in second trimester predictors of adverse pregnancy outcome?

Abstract: ObjectiveDuring pregnancy, inhibin A is mainly derived from the placenta and regulates the implantation and differentiation of embryos. Our aim was to assess whether second trimester serum inhibin A was associated with an increased risk of adverse pregnancy outcomes. MethodsWe investigated the serum levels of Inhibin A during the second trimester in pregnancy, and analyzed associations between the Inhibin A and the risk of adverse pregnancy outcome. 12,124 pregnant women were enrolled in this study between Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…reported a significant association between high inhibin levels and medically indicated preterm birth. This observation was also noted by other studies, 12,46 which concluded that the relationship between preterm birth and inhibin was secondary to other placenta‐mediated complications that may increase the risk of elective or emergency premature delivery.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…reported a significant association between high inhibin levels and medically indicated preterm birth. This observation was also noted by other studies, 12,46 which concluded that the relationship between preterm birth and inhibin was secondary to other placenta‐mediated complications that may increase the risk of elective or emergency premature delivery.…”
Section: Discussionsupporting
confidence: 79%
“…Recent literature supports an association between low levels of uE3 and adverse outcomes such as fetal growth restriction and spontaneous abortion 8 . A relationship also exists between high levels of inhibin and both pre‐eclampsia and preterm delivery, 12 whereas low inhibin in the first trimester has been associated with non‐viable pregnancies 13,14 …”
Section: Introductionmentioning
confidence: 97%
“… 21 Previous studies have reported that an increase of inhibin A is associated with adverse pregnancy outcomes, such as preeclampsia, fetal growth restriction, and preterm birth. 22 23 In contrast, there is limited information on the association between congenital malformation and an increased level of inhibin-A. 23 This study found an association between maternal serum inhibin-A in the second trimester with major fetal CHDs, but not with overall fetal cardiac defects.…”
Section: Discussionmentioning
confidence: 77%
“… 22 23 In contrast, there is limited information on the association between congenital malformation and an increased level of inhibin-A. 23 This study found an association between maternal serum inhibin-A in the second trimester with major fetal CHDs, but not with overall fetal cardiac defects. Women with high inhibin-A (≥2.5 MOM) had a 4.8-fold (95% CI 1.42–12.46) increased risk of major non-chromosomal fetal CHDs.…”
Section: Discussionmentioning
confidence: 77%
“…These biomarkers were originally selected for prenatal screening due to their combined predictive value for fetal aneuploidies ( 26 , 45 ). In all cases, they have also proven to be associated with fetal growth restriction and/or birthweight ( 11 , 46 51 ). Pregnancy associated plasma protein (PAPPA) is a metalloproteinase that is produced primarily by the placenta in early pregnancy and promotes insulin growth factor (IGF) binding to its receptor ( 52 ).…”
Section: Discussionmentioning
confidence: 99%